Asymmetric Epoxidation of Olefins with H2O2 Catalyzed by a Bioinspired Aminopyridine N4 Iron Complex. Issue 3 (18th January 2017) - Wang, Wenfang; Sun, Qiangsheng; Xu, Daqian; Xia, Chungu; Sun, Wei
Abstract: An iron complex with a chiral aminopyridine N4 ligand bearing strong electron‐donating and bulky morpholine groups on the ligand is synthesized and characterized. The iron complex serves to efficiently catalyze the asymmetric epoxidation of various olefins by employing aqueous hydrogen peroxide as the green oxidant, providing the corresponding epoxides in good to excellent yields and enantioselectivities (up to 93 % yield and 99.9 % ee ). Owing to the introduction of morpholine functional groups on the ligand, the Fe‐catalyzed reaction can proceed with a catalytic amount of the carboxylic acid partner (3 mol %). Abstract : Bioinspired and super selective : An aminopyridine N4 iron complex serves to efficiently catalyze the asymmetric epoxidation of various olefins by H2 O2, providing the epoxides in good to excellent yields and enantioselectivities (up to 99.9 % ee ). Owing to the introduction of morpholine functional groups on the ligand, the Fe‐catalyzed reaction can proceed with a catalytic amount of the carboxylic acid partner (3 mol %).